Psychometric Properties of the RESTQ-Sport-36 in a Collegiate Student-Athlete Population - Gnacinski, Stacy L.; Meyer, Barbara B.; Wahl, Carly A. (Frontiers in Psychology, 2021)
The purpose of the current study was to examine the reliability and validity of the RESTQ-Sport-36 for use in the collegiate student-athlete population. A total of 494 collegiate student-athletes competing in National Collegiate Athletic Association Division I, II, or III sanctioned sport completed the RESTQ-Sport-36 and Brief Profile of Mood States (POMS). Structural equation modeling (SEM) procedures were used to compare first order to hierarchical model structures. Results of a confirmatory factor analysis (χ2[528] = 1129.941, p < .001; SRMR = .050; CFI = .929) and exploratory structural equation modeling analysis (χ2[264] = 575.424, p < .001; SRMR = .013; CFI = .963) indicated that the first order 12-factor structure demonstrated the best fit of all models tested. Support was not observed for the fit of any hierarchical model. Moderate to strong correlations were observed between stress and recovery subscales and mood states, thus supporting the construct validity of the abbreviated RESTQ measurement model. The current findings provide support for the measure’s use in this population and give pause as it relates to the scoring and interpretation of hierarchical factors such as Total Stress and Total Recovery. Overall, the current results indicate that the RESTQ-Sport-36 may be a useful tool for collegiate student-athlete training load and competition monitoring.